Oocyte-derived growth factors promote development of antrum-like structures by porcine cumulus granulosa cells in vitro - Riho MORIKAWA; Hirohisa KYOGOKU; Jibak LEE; Takashi MIYANO (The Society for Reproduction and Development, 2022)
Oocytes communicate with the surrounding somatic cells during follicular development. We examined the effects of two oocyte-derived growth factors, growth differentiation factor 9 (GDF9) and bone morphogenetic protein 15 (BMP15), on the development of porcine oocyte-cumulus cell complexes (OCCs) in vitro. We collected OCCs from early antral follicles (1.2-1.5 mm) and prepared oocytectomized cumulus cell complexes (OXCs), which were then cultured in a growth medium supplemented with 0-100 ng/ml GDF9 and/or BMP15 for 7 days. In the medium without GDF9 or BMP15, OCCs developed during culture, and approximately 30% of them formed antrum-like structures. GDF9 promoted OCC development and structure formation in a dose-dependent manner. However, OXCs did not form antrum-like structures without growth factors. GDF9 promoted the development of OXCs, and 50 and 100 ng/ml GDF9 promoted the formation of the structures by 8% and 26%, respectively; however, BMP15 did not promote the formation of these structures. OXCs were then cultured with 100 ng/ml GDF9 and various concentrations of BMP15 to investigate their cooperative effects on the formation of antrum-like structures. BMP15 promoted the formation of antrum-like structures in a dose-dependent manner. In conclusion, GDF9 derived from oocytes is probably important for the formation of antrum-like structures in porcine OXCs, and BMP15 cooperates with GDF9 to form these structures.